Potential application of sulfonated expanded polystyrene impregnated in granular activated carbon in the removal of heavy metals in synthetic wastewater - Dinh Quang Hung (2008)
This study investigated the potential of using sulfonated expanded polystyrene impregnated on granular activated carbon (SPS-GAC) for the removal of heavy metals in synthetic wastewater. A successful method for producing dissolved sulfonated polystyrene (SPS) using oleum (60% by weight SO3) was developed. Values obtained from the ion exchange capacity are as follows: (1) for barium, 2.03E-05molBa/gSPS-GAC (2.79mgBa/gSPS-GAC) for SPS impregnated GAC as compared to 1.70E-06molBa/gGAC (0.24mg/gGA) for untreated GAC, (2) for copper, 8.34E-05molCu/gSPS-GAC (5.38mg/gSPS-GAC) for SPS impregnated GAC as compared to 5.66E-05molCu/gSPS-GAC (3.63mg/gGAC) for untreated GAC, and (3) for lead, 2.39E-05mol Pb/gSPS-GAC (5.13mg/gSPS-GAC) for SPS impregnated GAC as compared to 2.38E-05mol Pb/gGAC (4.92mg/gGAC) for untreated GAC. These results indicate that impregnation of SPS on GAC improves the removal of barium at concentration of 131.31 ppm and copper at concentration of 256.67 ppm but does not significantly contribute to the removal of lead with initial concentration of 156.34 ppm as compared with using untreated GAC.
"May 2008."
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Polystyrene; Sulfonation; Sewage -- Purification -- Heavy metals removal